Analysis Of Self-Concept And Self-Independence In The Behavior Of Disabled Group Who Perform Plastic Waste Recycle Business - Afrie Sweet Chris Deny Ekasari; Sandu Siyoto; Ema Mayasari (Universitas STRADA Indonesia, 2018)
The loss of one or more parts of a physical body that cannot functionproperly can affect a person's psyche and psychology, allowing anegative self-concept to arise. The purpose of this study was todetermine the Influence of Self-Concept and Self-Independence on theBehavior of Disabled Groups Who Conduct Plastic Waste RecyclingBusinesses.The research design is cross-sectional study, respondents were takenusing the Simple Random Sampling technique. The population of allpeople with disabilities is 74 people, the sample is 61 respondents.Independent variables are self-concept and self-independence in peoplewith disabilities, dependent variables are recycling behavior of plasticwaste, the results are analyzed using the Ordinal Regression test.The results of the study showed that the majority of respondents had agood self-concept, namely 33 respondents (54.1%), the majority ofrespondents were independent in carrying out activities, namely 42respondents (68.9%), almost half of the respondents had good behaviorin carrying out activities.recyclerubbishwhich is 29 respondents(47.5%). The results of the statistical test show a p value = 0.020 forself-concept so that H1 is accepted which means that there is aninfluence of self-concept on the behavior of groups of people withdisabilities who carry out plastic waste recycling efforts and a p value =0.030 for self-independence so that H1 is accepted which means thatthere is an influence of self-independence on the behavior of groups ofpeople with disabilities who carry out plastic waste recycling efforts.Self-concept and self-independence influence the behavior of groups ofpeople with disabilities who carry out plastic waste recycling efforts,where the higher the self-concept and the more independent peoplewith disabilities are in carrying out activities, the better the behavior ofcarrying out plastic waste recycling efforts.